2019
DOI: 10.7150/ijbs.30970
|View full text |Cite
|
Sign up to set email alerts
|

PCAT-1: A Novel Oncogenic Long Non-Coding RNA in Human Cancers

Abstract: Long non-coding RNAs (lncRNAs) are transcripts longer than 200 nucleotides (nts) without obvious protein coding potential. lncRNAs act as multiple roles in biological processes of diseases, especially carcinomas. Prostate cancer associated transcript-1 (PCAT-1) is an oncogenic lncRNA that identified by RNA-Sequence in prostate cancer. High expression of PCAT-1 is observed in different types of cancers, including prostate cancer, colorectal cancer, hepatocellular cancer and gastric cancer. High expressed PCAT-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 96 publications
0
24
0
Order By: Relevance
“…Recently, it is reported that lncRNAs play important roles in cellular functions, such as cell proliferation, apoptosis, invasion, gene regulation and chromatin remodeling 8. Moreover, large proportions of lncRNAs are involved in the cancer progression and metastasis 9, 10. The expression of lncRNAs is obviously tissue and cell type specific.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is reported that lncRNAs play important roles in cellular functions, such as cell proliferation, apoptosis, invasion, gene regulation and chromatin remodeling 8. Moreover, large proportions of lncRNAs are involved in the cancer progression and metastasis 9, 10. The expression of lncRNAs is obviously tissue and cell type specific.…”
Section: Introductionmentioning
confidence: 99%
“…2 Mounting evidence exists on the important participation of non-coding RNAs (ncRNAs), especially long ncRNAs (lncRNAs) and microRNAs (miRNAs), in the initiation and progression in the variety of tumors. 3 , 4 , 5 , 6 Efficient biomarkers among them have been identified for cancer diagnosis and prognosis evaluation. Thus, insight into molecular biomarkers for CRC could considerably facilitate clinical diagnosis and treatment and promote the survival time of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs), are a group of RNAs which identified as more than 200 nucleotides in length with limited protein coding potential [5]. A large number of research studies have demonstrated that more than 16 000 lncRNAs in the human transcriptome were frequently spliced, polyadenylated, and principally transcribed by RNA polymerase II, which might play multitudinous roles in cancer cellular life circles as proliferation, metastasis, epithelial-mesenchymal transition (EMT), apoptosis, and differentiation [6].…”
Section: Introductionmentioning
confidence: 99%